THE EFFECT OF PGR IN THE REGENERATION OF Arctium lappa - Chan, Men Yee (2018)
Herbs play an important role in traditional treatments of disease since ancient time. People are most likely to consume herbs because they have less toxicity and side effect when compare to chemical drugs. Arctium lappa, also called burdock, is a plant that commonly used in Traditional Chinese medicine. It can be used to cure sore throat and remove heavy metals such as mercury in the body. It also has high potential in cosmetic market and to treat cancer and HIV because many active compounds and antioxidant can be extracted from A. lappa. Antioxidant prevents the aging of skin and keeps the texture of the skin and the active compound extracted have anti-inflammatory, anti-tumor and anti-HIV properties therefore it is important to mass propagate this medicinal herb. Plant growth regulators (PGR) are commonly used to induce the growth of plants. The aim of this study is to determine the effect of PGR namely kinetin, benzyladenine (BA), indole-3-butyric acid (IAA), naphthalene acetic acid (NAA) in the regeneration of A. lappa. The fragments of the root of A. lappa were treated with kinetin, BA, IAA or NAA at different concentrations, 1, 2, 3, 4, 5 mg/L, the number of shoots formed was recorded for a period of three weeks. The results showed that only the first fragment of the root of A. lappa showed response to the different concentrations of exogenously applied PGRs. The best concentration of PGR to induce the leaves formation of A. lappa was 5 mg/L of kinetin which produced 14 leaves in the sample. BA and NAA were found to produce leaves at low concentrations whereas IBA induced leaf formation at high concentration.